Structuring and validation of a risk score to assess the level of pharmaceutical care for patients admitted to a hospital in Salvador (Research, Society and Development, 2024)
Objective: This study aims to develop and validate a score to identify the level of pharmaceutical care that will be provided to patients hospitalized in a tertiary hospital in Salvador, Bahia. Method: The present study took place over a period of one year (2022-2023) at reference hospital in Salvador. An online form was constructed containing several variables collected from the literature, which were later validated by the Delphi-Method. The evaluation of the experts occurred in two stages mediated by the Likert scale until reaching a consensus and finalizing the score. Finally, a pilot test was conducted to evaluate the agreement in the applicability of this score, based on the responses of a group of pharmacists using the weighted Kappa Cohen. Result: The pharmaceutical risk score was developed from the decisions of the specialists, considering eight variables such as the number of medications, age, comorbidities, and others capable of assessing the level of care that hospitalized patients demand, being responsible for assisting the pharmaceutical clinical practice. The model presented a weighted Kappa Cohen of 0.67 (p-value